Metal-free generation of hydroxyl radicals by benzoate-mediated decomposition of peroxides. Issue 54 (4th June 2020) - Zhang, Guoyang; Lu, Shuo; Zhang, Chun; Wu, Bingdang; Liang, Yong; Chen, Zhihao; Zhang, Li; Zhang, Shujuan
Abstract : A type of metal-free organic photo-Fenton-like reaction was developed using a combination of benzoates and peroxides for efficient generation of ˙OH. Abstract : A type of metal-free organic photo-Fenton-like reaction was developed, which was realized by a combination of UV with benzoates and peroxides. The findings here not only provide a novel ˙ OH production pathway, but also shed new light on the accurate quantification, better use or prevention of ˙ OH in many scenarios.